Studies on a putative mitochondrial DNA found in theileria parva. - Kairo, A.K. (University of London, 1993)
Theileria parva, a protozoan parasite of cattle, contains an extrachromosomal DNA molecule with an apparent mobility of 7.1 kb in agarose gels. 5893 bp of this DNA molecule have been fully sequenced and analysed. The sequence shows that it has the potential to code for apocytochrome b and polypeptide I and ill of cytochrome c oxidase protein which are components of the last two mitochondrial electron transport complexes. The DNA molecule also contains several unique short stretches of discontinuous sequences, which show high degree of sequence similarity to both large (LSU) and small (SSU) ribosomal subunit RNA of E.coli. Six fragmented rRNA like sequences, LSUI-LSU6 can be folded by intramolecular base pairing, into the phylogenetically conserved domains III, IV and V of the LSU rRNA. Five or possibly six fragments from the sequenced element have also been identified which show high sequence similarity to the E.coli SSU rRNA. These fragments have been folded by intra-molecular base pairing to form a structure similar to the conserved regions of the E.coli SSU RNA. The protein coding potential of the DNA molecule is characteristic of mitochondrial DNA and is very similar to extrachromosomal DNA molecules described in Plasmodium yoelii, P falciparum and the mitochondrial DNA of Chlamydomonas reinhardtii. The protein sequence of its cytochrome b is very homologous to the cytochrome b from a similar element described in Theileria annulata suggesting that they are of similar origin.